2020
DOI: 10.1002/pat.4985
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxybutyrate)‐based systems behavior on the controlled release of NPK fertilizers

Abstract: Here we investigate the behavior of controlled‐release systems based on poly(hydroxybutyrate) (PHB) to propose an actuation mechanism in a designed environment. Two formulations were produced employing 5% pure NPK fertilizer or 30% of bentonite nanoparticles (Bent) previously modified with NPK. The polymeric composites were obtained by melt processing and their thermal properties evaluated. The release of active compounds was evaluated by conductometric analysis in aqueous solutions at different pHs for 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, the melting temperature ( T m ) is lower for the first melting event, related to the PHB matrix, and similar for the second event, common to both PHB and PLA phases. This thermal behavior is known and widely reported in the literature, where the decrease in T m values is mainly associated with the formation of less perfect crystalline structures generated by the thermal degradation process of the PHB phase 25,26 …”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the melting temperature ( T m ) is lower for the first melting event, related to the PHB matrix, and similar for the second event, common to both PHB and PLA phases. This thermal behavior is known and widely reported in the literature, where the decrease in T m values is mainly associated with the formation of less perfect crystalline structures generated by the thermal degradation process of the PHB phase 25,26 …”
Section: Resultsmentioning
confidence: 58%
“…This thermal behavior is known and widely reported in the literature, where the decrease in T m values is mainly associated with the formation of less perfect crystalline structures generated by the thermal degradation process of the PHB phase. 25,26 Regarding to the addition of C30B, it is observed that the T m values are increased in relation to pure blend, and the magnitude of these increments is related with the mixing mode. In general, for the compounds where the nanoclay was previously mixed in only one phase, increments of around 5 C can be observed for the two melting peaks, while for the sample simultaneously mixed the T m values are very close to the original blend.…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…Ecovio ® is composed of PLA and poly(butylene adipate co-terephthalate) (PBAT) (Ecoflex ® ) and is a material with mechanical properties similar to those of traditional polymers used for agricultural applications [ 27 , 28 ]. Organophilic bentonite clays stand out among the inorganic nanoparticles applicable to the adsorption of fertilizers and their CRF biodegradable nanocomposites have greater matrix stability which allow for the slow release of agricultural compounds [ 5 , 29 ]. In addition to controlling drug release, nanoparticles can provide improvements in general properties of the composite, such as tensile strength, elastic modulus, flexural strength, flexural modulus [ 30 , 31 ], barrier properties [ 32 ] and thermal stability [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Doing so would not only reduce the dependence on petroleum based materials, but would also improve the valorization of the used residual streams. Moreover, the biodegradability of biopolymers makes them favorable to be used as a host material for functional fillers in order to become available through gradual exposure and/or diffusion from the matrix material [2][3][4]. Therefore, the production of slow-release fertilizers based on biopolymers and a functional filler material can become a reality.…”
Section: Introductionmentioning
confidence: 99%
“…If biochar could successfully be used as a filler to produce biocomposites, an additional advantage emerges in the biochars potential use as a slow release fertilizer. It was recently shown that PHB is indeed an interesting candidate as a matrix for controlled slow release of NPK fertilizers, positively affecting crop growth [4]. At the end of its life, the PHB matrix could even again be co-pyrolyzed with biomass to achieve a bio-oil with favorable characteristics as compared to conventional pyrolysis [23].…”
Section: Introductionmentioning
confidence: 99%